Influences of hypoxia exercise on whole-body insulin sensitivity and oxidative metabolism in older individuals - Chobanyan-Jürgens, Kristine (The journal of clinical endocrinology & metabolism, 2019)
We observed that 8 weeks of hypoxia training did not further enhance insulin sensitivity and markers of oxidative phosphorylation compared with endurance traini
Gesehen am 30.01.2020